Wahbah Zuhaili's View of Tawazun Suroh Al-jumu'ah Verses 9 -11 in Tafsir Al- Munir - Maisarah Siregar; Sulidar Sulidar (Edumaspul: Jurnal Pendidikan, 2024)
Tawazun is a concept in Islam that refers to balance, harmony, or proper proportion between various aspects of life. The purpose of this writing is to examine Wahbah Zuhaili's view of the concept of tawazun (balance) in his interpretation of Surah Al-Jumu'ah verses 9-11 contained in the Al-Munir commentary book. Through qualitative methods, this research identifies Zuhaili's approach to these verses, explores understanding of the concept of tawazun, and highlights its theological and practical meaning. The findings from this research indicate that Zuhaili understands tawazun as an important principle in religious and social life. Although there is no direct reference to Tawazun in Al-Munir's commentary. However, he emphasized the importance of maintaining a balance between worship and world affairs, as well as between rights and obligations, especially during Friday prayers. This concept explains integration within the broader framework of Islamic thought, providing a comprehensive view of how Muslims should live their lives with harmony and balance. It can be concluded that Zuhaili's understanding of tawazun provides valuable insight for Muslims in living life holistically in accordance with the teachings of the Islamic religion.